Stress-induced cardiomyopathy after nephrectomy in a patient with a kidney cancer: a case report - O. P. Kotova; S. V. Kotov; V. S. Shemenkova; V. G. Krasnov (Кардиоваскулярная терапия и профилактика)
Stress-induced (takotsubo) cardiomyopathy is a rare disease, which characterized by transient left ventricle dysfunction in response to a trigger factor (stress or severe somatic disease with surgical intervention) and is manifested by symptoms of acute coronary syndrome, but without significant coronary artery damage. In the population, the disease most often observes in postmenopausal women. Every year, more and more cases of takotsubo cardiomyopathy described in the literature, mainly after a severe stress. The presented article describes a case report of takotsubo cardiomyopathy after nephrectomy in a patient with comorbidity.